Sustainable tourism development digital strategy approach: case study of pokdarwis terong creative tourism village, Belitung Rege - Pinontoan, Nexen Alexandre; Lestari, Rini (Institute of Computer Science (IOCS), 2024)
This research discusses the development of sustainable tourism in the Terong Creative Tourism Village, with a focus on a holistic approach involving digitalization strategies with the aim of being an effective communication approach and able to provide social innovation and community empowerment. Through this holistic approach to outcome, various strategic elements interact and support each other in achieving sustainable tourism development goals. The results show that involving local communities in every stage of planning and implementing tourism projects with a digital approach is key to success, by ensuring the relevance, acceptance, and sustainability of the initiative. The use of digital technologies has played a crucial role in improving operational efficiency, expanding market reach, and strengthening sustainable practices. Social innovation has also been proven to have an added value impact on the tourism experience and strengthen community involvement in sustainable tourism development. Community empowerment is a key foundation in achieving success in sustainable tourism development, by prioritizing capacity building, training, and fair profit sharing. In conclusion, this holistic and adaptive approach ensures that tourism remains sustainable and relevant to changing market dynamics and socio-economic conditions. Sustainable collaboration between all stakeholders is also the key to success in sustainable tourism development in the future